A freeze-thaw resistant concrete material and its preparation method and application
By using modified water glass and basalt fiber in concrete, combined with the use of ultrasonic treatment and silane waterproofing agent, the problem of reduced durability of concrete in high-frequency freeze-thaw environments in severe cold areas has been solved, and efficient freeze-thaw resistance has been achieved. Performance and durability improvements.
Patent Information
- Application Number
- CN202211642190.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-20
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-12-20
AI Technical Summary
Concrete materials in severely cold areas are prone to freeze-thaw damage after undergoing high-frequency freeze-thawing, resulting in reduced structural durability and safety hazards.
By preparing a freeze-thaw resistant concrete material, using raw materials such as modified water glass and basalt fiber, combined with ultrasonic treatment and the use of silane waterproofing agent, the frost resistance and durability of concrete can be improved.
After 300 freeze-thaw tests indoors, the performance of the freeze-thaw resistant concrete material has not declined significantly, which significantly improves the durability of concrete in high-frequency freeze-thaw environments and meets the freeze-thaw resistance needs in severe cold areas.
Smart Images

Figure CN116253544B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of concrete materials, and in particular relates to a freeze-thaw resistant concrete material and a preparation method and application thereof. Background Art
[0002] Severely cold regions often have the characteristics of low temperature and large temperature difference between day and night. Concrete materials in these regions often experience high frequency of freeze-thaw, which often causes freeze-thaw damage to concrete materials, greatly reducing the durability of concrete structures, resulting in a greater threat to the safety and normal use of existing engineering structures. In particular, for concrete materials used in high-altitude and severely cold regions, more attention should be paid to the durability of the materials, and the antifreeze performance is the most important indicator of the durability of concrete in severely cold regions. Based on this, the present invention provides a freeze-thaw resistant concrete material and its preparation method and application, which has high antifreeze performance and meets the demand for concrete durability in severely cold regions. Summary of the invention
[0003] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a freeze-thaw resistant concrete material and a preparation method and application thereof.
[0004] The object of the present invention is achieved through the following technical scheme: A method for preparing a freeze-thaw resistant concrete material, comprising the following steps:
[0005] S1. Prepare the following raw materials by weight: 380-390 parts of ordinary Portland cement, 750-760 parts of medium sand, 1000-1100 parts of 5-31.5 mm graded crushed stone, 7.0-8.0 parts of polycarboxylate water reducer, 2.0-3.0 parts of basalt fiber, 20-22 parts of water glass, 0.004-0.0045 parts of disodium hydrogen phosphate, 0.0008-0.001 parts of basalt fiber powder, 0.2-0.22 parts of polyethylene glycol 200, and 180-200 parts of water;
[0006] S2. Preparation of modified water glass: disodium hydrogen phosphate, polyethylene glycol 200, basalt fiber powder and water glass are stirred and mixed by a magnetic stirrer, and then subjected to ultrasonic treatment for 10-15 minutes; the frequency of the ultrasonic treatment is 35-44 kHz;
[0007] S3. Preparation of concrete matrix: firstly dry-mix basalt fiber, medium sand and graded crushed stone until uniform, then add part of water for wet mixing, then add ordinary Portland cement, water reducing agent, modified water glass and remaining water for uniform mixing, and inject into the mold; the dry mixing time is 2-3 minutes;
[0008] S4. Curing of concrete matrix: Curing the prepared concrete matrix for 20-35 days; during curing, it is necessary to lay straw on the concrete surface for insulation treatment;
[0009] S5. Maintenance of freeze-thaw resistant concrete materials: Apply silane waterproofing agent on the surface of the cured concrete substrate and maintain again for 3-10 days.
[0010] Furthermore, in step S1, the basalt fiber has a length of 18 to 20 mm, a diameter of 13 to 18 μm, and a density of 2700 to 3000 kg / m 3 , the tensile strength is 3900~4800MPa.
[0011] Furthermore, in step S1, the modulus of the water glass is 2.0-2.5.
[0012] The ordinary Portland cement is P.O42.5 cement;
[0013] The medium sand is a debris particle with a particle size ranging from 0.5 mm to 0.25 mm;
[0014] Furthermore, in step S1, the diameter of the basalt fiber powder is 9-18 microns and the length is 30-50 microns. The basalt fiber powder is prepared by ball milling after chopped basalt fibers are ground to a size of more than 500 meshes.
[0015] Furthermore, the silane waterproofing agent is: a mixture of polytriethoxymethylsilane and silane emulsion, and the mass ratio of polytriethoxymethylsilane to silane emulsion is 5-7:4.
[0016] Furthermore, the dosage of the silane waterproofing agent is 200-300 g / m 2 .
[0017] Furthermore, the specific method of applying the silane waterproofing agent is: keep the surface of the concrete substrate clean and free of dust and slurry, and evenly apply the silane waterproofing agent more than 2 times, with an interval of 20-40 minutes between each application.
[0018] Preferably, the concrete surface is treated with a steel brush. First, the concrete surface slurry and dust are cleaned with a steel brush, and then the surface is cleaned with a blower. The silane waterproofing agent is evenly applied twice. The first application of the silane waterproofing agent is 100-150g / m 2 After natural drying for 30 minutes, apply waterproof silane antifreeze agent for the second time.
[0019] The present invention also provides a freeze-thaw resistant concrete material prepared by the method for preparing the freeze-thaw resistant concrete material.
[0020] The present invention also provides an application of the freeze-thaw resistant concrete material as cold-region tunnel lining concrete, canal concrete and dam structure concrete.
[0021] The principle of the present invention is:
[0022] Disodium hydrogen phosphate has high solubility in water glass, and phosphorus oxygen tetrahedron [PO4] and silicon oxygen tetrahedron [SiO4] will interweave to form a network structure, thereby increasing the adhesion of water glass; polyethylene glycol 200 increases the free hydroxyl groups in the water glass solution, reduces the degree of polymerization of the colloid particles in the water glass, and adheres to the surface of the gel colloid particles by hydrogen bonds or electrostatic attraction to form a polymer protective layer, thereby improving the surface potential energy and solvation ability of the silica gel colloid particles in the water glass, preventing the gel colloid particles from aggregating and growing, and obtaining uniform and fine gel colloid particles; ultrasonic waves input energy into the water glass system to refine the already gelled water glass colloid particles. At the same time, the basalt fiber powder will be evenly distributed in the water glass after ultrasonic treatment, slowing down the aging of the water glass and preventing the adhesion effect of the water glass from decreasing in a long-term low-temperature outdoor environment.
[0023] After the modified water glass is added to the concrete matrix, the uniform and fine gel particles in the modified water glass can more easily fill the gaps inside the concrete, and the silica gel produced during the hardening process can further block the gaps inside the concrete and change the pore structure of the concrete. By changing the void structure, the thermal conductivity of the concrete is reduced, and the impact of the external temperature on the concrete is reduced, thereby improving the concrete's anti-freeze and thaw ability.
[0024] By dry mixing the basalt fiber, medium sand and graded crushed stone, the basalt fiber and sand and gravel can be fully mixed, and the added basalt fiber can finally achieve coordinated deformation with the concrete, improve its tensile and impermeability properties, and thus change the frost resistance. The present invention selects specific basalt fiber specifications and dosages to improve the working performance of concrete, make the concrete hydration product more dense, and further improve the mechanical properties and durability of concrete.
[0025] The silane waterproofing agent applied on the surface penetrates 3 to 5 mm below the concrete surface, which can effectively isolate liquid water, making the concrete surface hydrophobic. The surface structure has a certain "lotus leaf effect", which can make the concrete have better waterproof and anti-freeze and thaw effects.
[0026] The beneficial effects of the present invention are:
[0027] The freeze-thaw resistant concrete material provided by the present invention has undergone 300 freeze-thaw tests indoors, and the performance of the test pieces has not been significantly reduced. The present invention can greatly improve the durability of concrete in a high-frequency freeze-thaw environment, and meet the freeze-thaw resistant use demand of concrete in severe cold areas. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1The results of freeze-thaw experiments on concrete prepared in Example 1 are shown in the figure on the left; the concrete prepared initially is shown in the figure on the right; the concrete after 150 freeze-thaw cycles is shown in the figure on the right;
[0029] Figure 2 The results of freeze-thaw experiments on concrete prepared in Comparative Example 1 are shown in the figure on the left. The figure on the right shows the concrete prepared initially, and the figure on the right shows the concrete after 150 freeze-thaw cycles.
[0030] Figure 3 The results of freeze-thaw experiments on concrete prepared in Comparative Example 2 are shown in the figure on the left; the concrete prepared initially is shown in the figure on the right; the concrete after 150 freeze-thaw cycles is shown in the figure on the right;
[0031] Figure 4 The results of freeze-thaw experiments on concrete prepared in Comparative Example 3 are shown in the figure on the left; the concrete prepared initially is shown in the figure on the right; the concrete after 150 freeze-thaw cycles is shown in the figure on the right;
[0032] Figure 5 The results of the freeze-thaw experiment of the concrete prepared in Comparative Example 4 are as follows; the left picture in the figure shows the initially prepared concrete, the middle picture shows the concrete after 150 freeze-thaw cycles, and the right picture shows the concrete after 200 freeze-thaw cycles. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings, but the protection scope of the present invention is not limited to the following.
[0034] Experimental conditions:
[0035] All raw materials involved in the examples of the present invention are commercially available, and Table 1 shows the specifications of each raw material.
[0036] Table 1
[0037]
[0038]
[0039] Example 1
[0040] Weigh 380 parts of ordinary Portland cement, 750 parts of medium sand, 1000 parts of 5-31.5 mm graded crushed stone, 7.0 parts of polycarboxylate water reducer, 2.0 parts of basalt fiber, 22 parts of water glass, 0.0045 parts of disodium hydrogen phosphate, 0.001 parts of basalt fiber powder, 0.2 parts of polyethylene glycol 200, and 200 parts of water according to weight parts;
[0041] Preparation of modified water glass: Disodium hydrogen phosphate, polyethylene glycol 200, basalt fiber powder and water glass were stirred and mixed by a magnetic stirrer, and then treated at an ultrasonic frequency of 40 kHz for 10 minutes to obtain modified water glass.
[0042] Preparation of concrete matrix: First, weighed basalt fiber, medium sand and graded crushed stone are dry-mixed in a mixer for 2.5 minutes, and then about 100 parts of water are added for wet mixing. Then, ordinary Portland cement, modified water glass, polycarboxylate water reducer and 100 parts of water are added, and stirring is continued to obtain a mixture.
[0043] Pour the mixture into the mold and vibrate to compact it.
[0044] Curing of concrete matrix: Curing the prepared concrete matrix for 28 days; laying straw for insulation treatment.
[0045] Preparation of freeze-thaw resistant concrete material: Use a steel brush to treat the surface of the concrete substrate after curing for 28 days. First, use a steel brush to clean the concrete surface slurry and dust, and then use a blower to clean the surface. Then, apply silane waterproofing agent to the surface of the concrete substrate after curing for 28 days. The application process is divided into two times. The first application of silane waterproofing agent is 150g / m 2 After natural drying for 30 minutes, apply 150g / m 2 Silane water repellent.
[0046] Curing of freeze-thaw resistant concrete materials: Curing the concrete substrate coated with silane waterproofing agent in a dry environment for 8 days.
[0047] Example 2
[0048] Weigh 390 parts of ordinary Portland cement, 760 parts of medium sand, 1080 parts of 5-31.5 mm graded crushed stone, 8.0 parts of polycarboxylate water reducer, 2.5 parts of basalt fiber, 20 parts of water glass, 0.0040 parts of disodium hydrogen phosphate, 0.001 parts of basalt fiber powder, 0.2 parts of polyethylene glycol 200, and 180 parts of water according to weight parts;
[0049] Preparation of modified water glass: Disodium hydrogen phosphate, polyethylene glycol 200, basalt fiber powder and water glass were stirred and mixed by a magnetic stirrer, and then treated at an ultrasonic frequency of 40 kHz for 10 minutes to obtain modified water glass.
[0050] Preparation of concrete matrix: First, weighed basalt fiber, medium sand and graded crushed stone are dry-mixed in a mixer until uniform. The dry mixing time is 2.5 minutes. Then, about 90 parts of water are added for wet mixing. Then, ordinary Portland cement, modified water glass, polycarboxylate water reducer and 90 parts of water are added. The mixture is stirred evenly to obtain a mixture.
[0051] Pour the mixture into the mold and vibrate to compact it.
[0052] Curing of concrete matrix: Curing the prepared concrete matrix for 28 days; laying straw for insulation treatment.
[0053] Preparation of freeze-thaw resistant concrete material: Use a steel brush to treat the surface of the concrete substrate after curing for 28 days. First, use a steel brush to clean the concrete surface slurry and dust, and then use a blower to clean the surface. Then, apply silane waterproofing agent to the surface of the concrete substrate after curing for 28 days. The application process is divided into two times. The first application of silane waterproofing agent is 150g / m 2 After natural drying for 30 minutes, apply 150g / m 2 Silane water repellent.
[0054] Curing of freeze-thaw resistant concrete materials: Curing the concrete substrate coated with silane waterproofing agent in a dry environment for 8 days.
[0055] Comparative Example 1 (the difference between Comparative Example 1 and Example 1 is that no modified water glass is added, no basalt fiber is added, and no silane waterproofing agent is applied externally)
[0056] The formula of comparative example 1 is: 390 parts of ordinary Portland cement, 760 parts of medium sand, 1080 parts of 5-31.5 mm graded crushed stone, 8.0 parts of polycarboxylate water reducer, and 180 parts of water;
[0057] Preparation of concrete matrix: directly mix all raw materials evenly using a mixer to obtain a mixture.
[0058] Pour the mixture into the mold and vibrate to compact it.
[0059] Curing of concrete matrix: Curing the prepared concrete matrix for 28 days; laying straw for insulation treatment.
[0060] Comparative Example 2 (the difference between Comparative Example 2 and Example 1 is that ordinary water glass is used instead of modified water glass)
[0061] The formula of comparative example 2 is: 390 parts of ordinary Portland cement, 760 parts of medium sand, 1080 parts of 5-31.5 mm graded crushed stone, 8.0 parts of polycarboxylate water reducer, 2.5 parts of basalt fiber, 20 parts of water glass, and 180 parts of water;
[0062] Preparation of concrete matrix: First, weighed basalt fiber, medium sand and graded crushed stone are dry-mixed in a mixer until uniform. The dry mixing time is 2.5 minutes. Then, about 90 parts of water are added for wet mixing. Then, ordinary Portland cement, water glass, polycarboxylate water reducer and 90 parts of water are added. The mixture is stirred evenly to obtain a mixture.
[0063] Pour the mixture into the mold and vibrate to compact it.
[0064] Curing of concrete matrix: Curing the prepared concrete matrix for 28 days; laying straw for insulation treatment.
[0065] Preparation of freeze-thaw resistant concrete material: Use a steel brush to treat the surface of the concrete substrate after curing for 28 days. First, use a steel brush to clean the concrete surface slurry and dust, and then use a blower to clean the surface. Then, apply silane waterproofing agent to the surface of the concrete substrate after curing for 28 days. The application process is divided into two times. The first application of silane waterproofing agent is 150g / m 2 After natural drying for 30 minutes, apply 150g / m 2 Silane water repellent.
[0066] Curing of freeze-thaw resistant concrete materials: Curing the concrete substrate coated with silane waterproofing agent in a dry environment for 8 days.
[0067] Comparative Example 3 (the difference between Comparative Example 3 and Example 1 is that the preparation method of modified water glass is different. Comparative Example 3 uses disodium hydrogen phosphate and basalt fiber powder to modify water glass)
[0068] The formula of comparative example 3 is: 380 parts of ordinary Portland cement, 750 parts of medium sand, 1000 parts of 5-31.5 mm graded crushed stone, 7.0 parts of polycarboxylate water reducer, 2.0 parts of basalt fiber, 22 parts of water glass, 0.001 parts of basalt fiber powder, 0.0045 parts of disodium hydrogen phosphate, and 200 parts of water;
[0069] Preparation of modified water glass: Disodium hydrogen phosphate, basalt fiber powder and water glass were stirred and mixed by a magnetic stirrer, and then treated at an ultrasonic frequency of 40 kHz for 10 minutes to obtain modified water glass.
[0070] Preparation of concrete matrix: First, weighed basalt fiber, medium sand and graded crushed stone are dry-mixed in a mixer for 2.5 minutes, and then about 100 parts of water are added for wet mixing. Then, ordinary Portland cement, modified water glass, polycarboxylate water reducer and 100 parts of water are added, and stirring is continued to obtain a mixture.
[0071] Pour the mixture into the mold and vibrate to compact it.
[0072] Curing of concrete matrix: Curing the prepared concrete matrix for 28 days; laying straw for insulation treatment.
[0073] Preparation of freeze-thaw resistant concrete material: Use a steel brush to treat the surface of the concrete substrate after curing for 28 days. First, use a steel brush to clean the concrete surface slurry and dust, and then use a blower to clean the surface. Then, apply silane waterproofing agent to the surface of the concrete substrate after curing for 28 days. The application process is divided into two times. The first application of silane waterproofing agent is 150g / m 2 After natural drying for 30 minutes, apply 150g / m 2 Silane water repellent.
[0074] Curing of freeze-thaw resistant concrete materials: Curing the concrete substrate coated with silane waterproofing agent in a dry environment for 8 days.
[0075] Comparative Example 4 (the difference between Comparative Example 4 and Example 1 is that the preparation method of modified water glass is different. Comparative Example 4 uses disodium hydrogen phosphate and polypropylene fiber powder to modify water glass; and uses the same volume of polypropylene fiber to replace basalt fiber)
[0076] 380 parts of ordinary Portland cement, 750 parts of medium sand, 1000 parts of 5-31.5mm graded crushed stone, 7.0 parts of polycarboxylate water reducer, 0.7 parts of polypropylene fiber, 22 parts of water glass, 0.001 parts of polypropylene fiber powder, 0.0045 parts of disodium hydrogen phosphate, and 200 parts of water;
[0077] Preparation of modified water glass: Disodium hydrogen phosphate, polypropylene fiber powder and water glass were stirred and mixed using a magnetic stirrer, and then treated at an ultrasonic frequency of 40 kHz for 10 minutes to obtain modified water glass.
[0078] Preparation of concrete matrix: First, the weighed polypropylene fiber, medium sand and graded crushed stone are dry-mixed in a mixer for 2.5 minutes, and then about 100 parts of water are added for wet mixing. Then, ordinary Portland cement, modified water glass, polycarboxylic acid water reducer and 100 parts of water are added, and stirring is continued to obtain a mixture.
[0079] Pour the mixture into the mold and vibrate to compact it.
[0080] Curing of concrete matrix: Curing the prepared concrete matrix for 28 days; laying straw for insulation treatment.
[0081] Preparation of freeze-thaw resistant concrete material: Use a steel brush to treat the surface of the concrete substrate after curing for 28 days. First, use a steel brush to clean the concrete surface slurry and dust, and then use a blower to clean the surface. Then, apply silane waterproofing agent to the surface of the concrete substrate after curing for 28 days. The application process is divided into two times. The first application of silane waterproofing agent is 150g / m 2 After natural drying for 30 minutes, apply 150g / m 2 Silane water repellent.
[0082] Curing of freeze-thaw resistant concrete materials: Curing the concrete substrate coated with silane waterproofing agent in a dry environment for 8 days.
[0083] Experimental Example 1 Rapid Freeze-Thaw Test Performance Test
[0084] According to GB / T50082-2009 "Standard for Experimental Methods of Long-term Performance and Durability of Ordinary Concrete", the rapid freeze-thaw test performance test was carried out. The following results were obtained:
[0085] Table 1 Freeze-thaw test results
[0086]
[0087] “ / ” indicates that the specimen has reached the specification standard or has been damaged by freeze-thaw.
[0088] from Figure 1-5 From the freeze-thaw test results and the photos of concrete specimens in the test process in Table 1, the following conclusions can be drawn: the modified water glass of the present invention is used for basalt fiber concrete, and combined with the method of applying silane waterproofing agent on the surface, after 300 freeze-thaw tests indoors, the frost resistance of concrete can be significantly improved, the durability of concrete can be improved, and the durability of concrete in a high-frequency freeze-thaw environment can be greatly improved, thus meeting the freeze-thaw resistance demand of concrete in severe cold areas.
[0089] The above is only a preferred embodiment of the present invention. It should be understood that the present invention is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art shall not deviate from the spirit and scope of the present invention, and shall be within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a freeze-thaw resistant concrete material, characterized in that: The following steps are involved: S1. Prepare the following raw materials by weight: 380-390 parts of ordinary Portland cement, 750-760 parts of medium sand, 1000-1100 parts of 5-31.5 mm graded crushed stone, 7.0-8.0 parts of polycarboxylate water reducer, 2.0-3.0 parts of basalt fiber, 20-22 parts of water glass, 0.004-0.0045 parts of disodium hydrogen phosphate, 0.0008-0.001 parts of basalt fiber powder, 0.2-0.22 parts of polyethylene glycol 200, and 180-200 parts of water; S2. Preparation of modified water glass: disodium hydrogen phosphate, polyethylene glycol 200, basalt fiber powder and water glass are stirred and mixed, and ultrasonically treated for 10-15 minutes; the frequency of the ultrasound is 35kHz-44kHz; S3, preparation of concrete matrix: firstly dry-mix basalt fiber, medium sand and graded crushed stone until uniform, then add part of water to wet-mix, then add ordinary Portland cement, water reducing agent, modified water glass and remaining water to mix uniformly, and inject into the mold; S4. Curing of the concrete matrix: curing the prepared concrete matrix for 20-35 days; S5. Maintenance of freeze-thaw resistant concrete materials: Apply silane waterproofing agent on the surface of the cured concrete substrate and maintain again for 3-10 days.
2. The method for preparing a freeze-thaw resistant concrete material according to claim 1, characterized in that: In step S1, the basalt fiber has a length of 18-20 mm, a diameter of 13-18 μm, and a density of 2700-3000 kg / m 3 , the tensile strength is 3900~4800MPa.
3. The method for preparing a freeze-thaw resistant concrete material according to claim 1, characterized in that: In step S1, the modulus of the water glass is 2.0-2.
5.
4. The method for preparing a freeze-thaw resistant concrete material according to claim 1, characterized in that: In step S1, the basalt fiber powder has a diameter of 9-18 microns and a length of 30-50 microns.
5. The method for preparing a freeze-thaw resistant concrete material according to claim 1, characterized in that: The silane waterproofing agent is a mixture of polytriethoxymethylsilane and silane emulsion, and the mass ratio of polytriethoxymethylsilane to silane emulsion is 5-7:
4.
6. The method for preparing a freeze-thaw resistant concrete material according to claim 1, characterized in that: The dosage of the silane waterproofing agent is 200-300 g / m 2 .
7. The method for preparing a freeze-thaw resistant concrete material according to claim 1, characterized in that: The specific method of applying silane waterproofing agent is: keep the surface of the concrete substrate clean and free of dust and slurry, and apply the silane waterproofing agent evenly for more than 2 times, with an interval of 20-40 minutes between each application.
8. The freeze-thaw resistant concrete material prepared by the method for preparing a freeze-thaw resistant concrete material according to any one of claims 1 to 7.
9. Application of the freeze-thaw resistant concrete material according to claim 8 as tunnel lining concrete, canal concrete and dam structure concrete in cold regions.
Citation Information
Patent Citations
Marine concrete with high freeze thawing resistance as well as preparation method thereof
CN110759702A